2013
DOI: 10.1017/s0950268813000496
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in norovirus shedding duration affects community risk

Abstract: Norovirus is a common cause of gastroenteritis in all ages. Typical infections cause viral shedding periods of days to weeks, but some individuals can shed for months or years. Most norovirus risk models do not include these long-shedding individuals, and may therefore underestimate risk. We reviewed the literature for norovirus-shedding duration data and stratified these data into two distributions: regular shedding (mean 14-16 days) and long shedding (mean 105-136 days). These distributions were used to info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 48 publications
(60 reference statements)
1
30
1
2
Order By: Relevance
“…Similarly, Ayukekbong et al [34] reported that in developing countries NoV infections are very common with comparable detection rates observed in diarrhea cases and controls. However in a cross-sectional study, it is easy to mis-classify substantial numbers of post-symptomatic infections as asymptomatic infections even when the controls are defined as absence of diarrhea symptoms in the preceding 4 weeks [35], [36], [37].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Ayukekbong et al [34] reported that in developing countries NoV infections are very common with comparable detection rates observed in diarrhea cases and controls. However in a cross-sectional study, it is easy to mis-classify substantial numbers of post-symptomatic infections as asymptomatic infections even when the controls are defined as absence of diarrhea symptoms in the preceding 4 weeks [35], [36], [37].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is heterogeneity in the duration of shedding. Milbrath et al developed a NoV transmission model based on NoVshedding data and concluded that long-term (105-to 136-day) shedders increase the probability of an outbreak by 33% and the severity of transmission (as measured by the attack rate) by 20% (51). Therefore, knowledge of the duration of NoV shedding can help inform NoV risk management strategies.…”
Section: Contamination Sourcesmentioning
confidence: 99%
“…64,65 Long-term shedding was described among children less than 6 months, 63 in elderly, 64 hospitalized and immunosuppressed patients. 62 Predictive modeling of viral shedding classifies shedding into regular shedding with a mean of 14-16 d and long shedding with a mean ranging between 105 and 136 d 66 Recent studies suggest the lack of a significant difference of virus shedding between asymptomatic and symptomatic NoV infections despite the individual variation in virus peak levels detected in stool. 67,68 This study reported different viral shedding activities as compared to previous reports 7,69 whereby infected adults shed virus during a range of 15-56 d. The authors argued that the variable results in NoV shedding might be due to the use of different PCR techniques to detect the virus.…”
Section: Viral Shedding Natural Infection With Nov and Seroprotectionmentioning
confidence: 99%